Pengembangan Media Pembelajaran Berbantu Google Sites pada Pembelajaran Tematik Tema 4 Subtema 1 Kelas V SDN 11 Pontianak Kota - Wahfiudin, Muhamad; Salimi, Asmayani; Ghasya, Dyoty Auliya Vilda; Halidjah, Siti; Pranata, Rio (FONDATIA, 2023)
Making learning media supported by Google sites for Theme 4, Sub Theme 1, Learning 1 material is the purpose of this research. Borg and Gall's development research used nine of the ten development steps, including potential problems, data collection, design, design validation, design revision, initial trial, product revision, trial use, and product revision. Quantitative data was obtained from the results of validator product evaluations and teacher and student responses to the media practicability questionnaire. Validators, teachers, and students provided suggestions and notes that became the source of qualitative data. Interview guidelines, questionnaires, and documentation are examples of research tools. The results of the assessment by media and material experts are used to determine the feasibility level of a learning media, while the teacher and student assessments are used to determine the practicality level of a learning media. The average media expert validation score of 4.4 which meets the criteria of "very valid" puts the product in the "very feasible" category for use in the field. The material expert validation results get an average of 4.2 with the criteria "very valid" which means the product is included in the "very feasible" category for use in the field. The results of the evaluation of the practicality of learning media by small groups obtained an average of 3.31 with the criteria "very practical". The results of the evaluation of the practicality of learning media by large groups obtained an average of 3.39 with the criteria "very practical". The media obtained an average score of 3.78 with the criteria of "very practical" according to the teacher's assessment of its practicality.